An ancestral core haplotype defines the critical region harbouring the North Carolina macular dystrophy gene (MCDR1). - Sauer, Christian; Schworm, H. D.; Ulbig, M.; Blankenagel, Anita; Rohrschneider, Klaus; Pauleikhoff, D.; Grimm, T.; Weber, B. H. (Journal of medical genetics, 1997)
Autosomal dominant North Carolina macular dystrophy (NCMD) or central areolar pigment epithelial dystrophy (CAPED) is an allelic disorder that maps to an approximately 7.2 cM interval between DNA markers at D6S424 and D6S1671 on 6q14-q16.2. The further refinement of the disease locus has been hindered by the lack of additional recombination events involving the critical region. In this study, we have identified three multigeneration families of German descent who express the NCMD phenotype. Genotyping was carried out with a series of markers spanning approximately 53 cM around the NCMD locus, MCDR1. Genetic linkage between the markers and the disease phenotype in each of the families could be shown. Disease associated haplotypes were constructed and provide evidence for an ancestral founder for the German NCMD families. This haplotype analysis suggests that a 4.0 cM interval flanked by markers at D6S249 and D6S475 harbours the gene causing NCMD, facilitating further positional cloning approaches.